2014
DOI: 10.1021/ja504670k
|View full text |Cite
|
Sign up to set email alerts
|

Azulene Methacrylate Polymers: Synthesis, Electronic Properties, and Solar Cell Fabrication

Abstract: We report the synthesis of novel azulene-substituted methacrylate polymers by free radical polymerization, in which the azulene moieties represent hydrophobic dipoles strung pendant to the polymer backbone and impart unique electronic properties to the polymers. Tunable optoelectronic properties were realized by adjusting the azulene density, ranging from homopolymers (having one azulene group per repeat unit) to copolymers in which the azulene density was diluted with other pendant groups. Treating these poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
53
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 37 publications
1
53
0
2
Order By: Relevance
“…4 For example, azulene derivatives have been used for developing advanced organic materials, including liquid crystals, 5 molecular switches, 6 anion receptors/sensors, 7 nonlinear optical materials, 8 organic/polymeric conductors, 9 and near-infrared resonance materials. 10 In recent years, azulene derivatives have attracted ever increasing attention due to their successful applications in organic electronic and photovoltaic devices, such as organic field-effect transistors (OFETs), 11 organic photovoltaics (OPVs), 12 and perovskite solar cells. 13 …”
Section: Introductionmentioning
confidence: 99%
“…4 For example, azulene derivatives have been used for developing advanced organic materials, including liquid crystals, 5 molecular switches, 6 anion receptors/sensors, 7 nonlinear optical materials, 8 organic/polymeric conductors, 9 and near-infrared resonance materials. 10 In recent years, azulene derivatives have attracted ever increasing attention due to their successful applications in organic electronic and photovoltaic devices, such as organic field-effect transistors (OFETs), 11 organic photovoltaics (OPVs), 12 and perovskite solar cells. 13 …”
Section: Introductionmentioning
confidence: 99%
“…10,35,36 Therefore, upon the treatment of trifluoroacetic acid (TFA), π-electron drift from the sevenmembered ring of azulene to the five-membered ring generates cycloheptatrienyl (tropylium) cation and makes azulene become a strong electron-acceptor. 2,37 Significant redistribution of charge is formed and generates distinct charge separation. As a result, substantial charge transfer from HOMO to LUMO after excitation leads to strong ICT which could lower the bandgap and result in long wavelength absorption.…”
Section: ■ Introductionmentioning
confidence: 99%
“…[3][4][5] Similarly, the physical, electronic, and optical properties of some natural pigments could offer access to key building blocks for developing bio-derived chromophoric materials. [9][10][11][12][13][14][15][16] Chemically, guaiazulene is a nonalternant hydrocarbon that is notable for its low transition energy to the S 1 state and unusually large S 1 -S 2 gap, [17][18][19][20][21][22][23][24][25][26][27] where S 1 and S 2 refer to the first and second electronically excited states, respectively. 3,8 Among known natural pigments, 6-8 guaiazulene has received recent popularity for its interesting physical and electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…6-8 Additionally, the non-toxic nature and the accompanying eco-friendly feature of natural dyes could set the stage for chemists to develop "green" routes towards photonic and conductive materials. [17][18][19][20][21][22][23][24][25][26][27] It was shown that extending the conjugation through the seven-membered ring of the parent azulene with aromatic substituents dramatically impacts the optical, electrochemical, and electrochromic properties of the azulenylium carbocation. [9][10][11][12][13][14][15][16][17] As a nontoxic natural product found in the oils of Guajacum officinale and Matricaria chamomilla, as well as in the vibrant-blue mushroom Lactarius indigo, guaiazulene has been approved by the FDA as a cosmetic color additive.…”
Section: Introductionmentioning
confidence: 99%